Damage index model and hysteretic viscous damping of masonry infill walls subjected to out-of-plane loadings - Furtado, André (2022)
The definition of damage states for structural and non-structural elements is necessary to support the seismic vulnerability analyses and identify the most vulnerable elements that need to be retrofitted. The studies related to masonry infill walls focused on multiple experimental studies to characterize their in-plane and/or out-of-plane (OOP) behaviour. Some codes have already proposed damage states for masonry infill walls only under in-plane loadings. Also, the study of the normalized energy dissipation and the hysteretic viscous damping when subjected to OOP loadings were not explored. It is recognized that the OOP behaviour of masonry infill walls is still nowadays a topic needing further investigations. The main objective of this work is to propose damage index for infill walls under to pure OOP seismic loadings. For that, a detailed analysis of the damage observed in masonry infill walls tested under pure OOP loadings was performed. The damage observed in masonry infill walls made with different masonry units, with and without openings, is carefully detailed. After that, a pilot damage index model is proposed for masonry infill walls made of hollow clay horizontal brick units. The third objective of this work was the assessment and discussion of their normalized energy dissipation capacity and their hysteretic viscous damping. Some analytical formulations were proposed to estimate these parameters. A database containing thirteen OOP tests performed by three different authors was used to achieve these goals.